The Effect of 6-Benzylaminopurine and Media on in vitro Culture of Mamao Dong (Antidesma bunius (L.) Spreng. var. bunius) - เทิดบารมี, พรทิพย์ (KKU Science Journal, 2014)
The objectives of this study were to investigate the most effective methods for surfacesterilization of shoot explants and the most suitable media for in vitro induction of shoot multiplication and promotion of shoot growth of Mamao Dong (Antidesma bunius (L.) Spreng. var. bunius). The media used for shoot multiplication included Murashige and Skoog (MS) and Woody Plant Medium (WPM) supplemented with 0, 1, 3 and 5 mg/l 6-Benzylaminopurine (6- BAP). For induction of roots, full-, half- and quarter-strength WPM (WPM, ½ WPM and ¼ WPM) were tested. The most effective method for sterilizing the shoots was to soak the intact shoots for 1 minute in 70% (v/v) ethyl alcohol before cutting the shoots from the stem followed by soaking in 2.4% sodium hypochlorite for 10 minutes and finally in 1.2% (v/v) sodium hypochlorite for another 10 minutes. This sterilization process resulted in the highest percentage of shoot explants which were uncontaminated and survived (83.33%). Culture of shoots in MS containing 1 mg/l 6-BAP for 8 weeks produced maximum average number of shoots (2.7) which were 2.85 cm long on average. WPM supplemented with 1 and 3 mg/l were suitable for shoot induction and growth producing the maximum of 2.9 shoots (2.76 cm long) and 2.3 shoots (2.52 cm long), respectively. Culturing the shoots in full-strength and ¼ strength WPM for 8 weeks produced highest percentage of root induction (10%).